Neuromuscular involvement in COVID-19 critically ill patients. Issue 12 (December 2020) - Cabañes-Martínez, Lidia; Villadóniga, Marta; González-Rodríguez, Liliana; Araque, Lesly; Díaz-Cid, Alba; Ruz-Caracuel, Ignacio; Pian, Héctor; Sánchez-Alonso, Susana; Fanjul, Samira; del Álamo, Marta; Regidor, Ignacio
Highlights: Many COVID-19 patients require ICU stay which can result in neuromuscular damage. We describe a series of patients with the diagnosis of ICU acquired weakness. Neurophysiology plays an essential role in the diagnosis of these patients. Abstract: Objective: Coronavirus disease 2019 (COVID-19) has a high incidence of intensive care admittance due to the severe acute respiratory syndrome (SARS). Intensive care unit (ICU)-acquired weakness (ICUAW) is a common complication of ICU patients consisting of symmetric and generalised weakness. The aim of this study was to determine the presence of myopathy, neuropathy or both in ICU patients affected by COVID-19 and whether ICUAW associated with COVID-19 differs from other aetiologies. Methods: Twelve SARS CoV-2 positive patients referred with the suspicion of critical illness myopathy (CIM) or polyneuropathy (CIP) were included between March and May 2020. Nerve conduction and concentric needle electromyography were performed in all patients while admitted to the hospital. Muscle biopsies were obtained in three patients. Results: Four patients presented signs of a sensory-motor axonal polyneuropathy and seven patients showed signs of myopathy. One muscle biopsy showed scattered necrotic and regenerative fibres without inflammatory signs. The other two biopsies showed non-specific myopathic findings. Conclusions: We have not found any distinctive features in the studies of the ICU patients affected by SARS-CoV-2 infection. Significance: Further studies are needed to determine whether COVID-19-related CIM/CIP has different features from other aetiologies. Neurophysiological studies are essential in the diagnosis of these patients.